Ways of retracing tracks: memory, oblivion, nostalgia - Campra, Rosalba (Romanica Olomucensia, 2020)
Arising from a personal childhood experience, the choice of memory appears as a recurring theme in the author's theoretical, critical, and creative writing. All these forms are used in this paper as an exemplification for research in the bordering areas of memory, oblivion, and nostalgia. The definition of these semantic areas as proposed in dictionaries, just like their metaphors in literature, is explored in their convergences and contradictions, giving rise to a series of questions that position the individual in relation to the collective and highlight the function of discourse as a guarantee of persistence in a continually renewed present. On the one hand the itinerary shows the strategies (conceived as architectural images) for recuperating the individual memory, while on the other hand it unveils the explicit or surreptitious politics for denying the collective history (focusing on Latin American countries), as well as the mechanisms of denunciation and defence elaborated to contrast them. Through this research a return route is drawn to a kind of paradise: the archetype of a dwelling that is invulnerable to time. Participation in the memory of others cannot then be restricted to the category of the impossible; on the contrary, it suggests a way of "retracing the tracks" that art reverberates on to reality, conveying it into a shared experience.
Keywords: Rosalba Campra; memory; persistence; denial; reconstruction; invention